Utilization of Satellite Imagery and GIS for Mapping Potential Anchovy Fishing Areas in East Lampung - Rifki Arif Rifki; Chairani Chairani; Sriyanto Sriyanto (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This study utilises Aqua MODIS satellite imagery from January to December 2023 to analyse Sea Surface Temperature (SST) and chlorophyll-a as primary indicators in mapping Potential Fishing Zones (PFZ) for anchovy in East Lampung. Images were filtered based on minimal cloud cover and seasonal completeness using Level 3 daily data with 1 km resolution. The spatial analysis was conducted using Geographic Information Systems (GIS) to identify areas with SST between 29–31°C and chlorophyll-a concentrations above 0.2 mg/m³, which are considered optimal for anchovy habitat. The results show dynamic seasonal shifts in fishing zones influenced by oceanographic conditions. Compared to previous studies, this research provides more detailed seasonal maps and incorporates local fishing data to strengthen relevance. Despite limitations in temporal continuity due to cloud coverage, the approach demonstrates potential for efficient and sustainable fisheries management in Lampung.